Engineering acoustics : noise and vibration control - Crocker, Malcolm J.; Arenas, Jorge P. (Wiley series in acoustics noise and vibration, 2021)
"A comprehensive evaluation of the basic theory for acoustics, noise and vibration control together with fundamentals of how this theoretical material can be applied to real world problems in the control of noise and vibration in aircraft, appliances, buildings, industry, and vehicles. The basic theory is presented in elementary form and only of sufficient complication necessary to solve real practical problems. Unnecessary advanced theoretical approaches are not included. In addition to the fundamental material discussed, chapters are included on human hearing and response to noise and vibration, acoustics and vibration transducers, instrumentation, noise and vibration measurements, and practical discussions concerning : community noise and vibration, interior and exterior noise of aircraft, road and rail vehicles, machinery noise and vibration sources, noise and vibration in rapid transit rail vehicles, automobiles, trucks, off road vehicles, and ships. In addition, extensive up to date useful references are included at the end of each chapter for further reading. The book concludes with a glossary on acoustics, noise and vibration"--